#### Answer

Inconsistent

#### Work Step by Step

$x$ = 9 + $y$
-(9+$y$) + $y$ = 1
-9 - $y$ + $y$ = 1
-9 = 1
-9$\ne$1, so it has no solution.

Published by
Cengage Learning

ISBN 10:
1-13311-087-8

ISBN 13:
978-1-13311-087-3

Inconsistent

$x$ = 9 + $y$
-(9+$y$) + $y$ = 1
-9 - $y$ + $y$ = 1
-9 = 1
-9$\ne$1, so it has no solution.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.